Asian tigers and the Chinese dragon: Competition and collaboration between sentinels of pandemics from SARS to COVID‐19. (27th July 2020) - Keck, Frédéric
Abstract: This article compares the management of COVID‐19 in different Asian states—China, Hong Kong, Singapore, Taiwan, South Korea, Japan, and Vietnam—after their reactions to the SARS crisis in 2003. It uses animal metaphors and the concept of sentinel territory to describe the way these states have prepared for the next pandemic crisis in a mix of competition and collaboration that produces solidarity.